Broken-crescent sign at CT indicates impending aortic rupture in patients with acute aortic intramural hematoma - Ko, Sheung-Fat (Insights Imaging, 2020)
BACKGROUND: This retrospective study evaluated the computed tomography (CT) features and clinical implications of a novel broken-crescent sign in patients with acute aortic intramural hematoma (IMH). METHODS: Out of 104 patients with aortic IMH encountered in our institution between 2003 and 2018, nine patients exhibited a positive broken-crescent sign, which was defined as a focal defect within the hyper-attenuating crescentic IMH on unenhanced CT, corresponding to a smooth out-bulging of the aortic lumen on enhanced study. The clinical findings, CT features, and outcomes of these nine patients were analyzed. RESULTS: Of five males and four females (age range 48–84 years, mean 69.7 years), six had type A and three had type B IMH. Five patients who had medical treatment and stable status for 1 to 3 days suffered sudden death, two of whom showed ascending aortic rupture with hemopericardium in one and adventitial tear with outward spillage of IMH in another at follow-up CT. The other four patients had early surgical or endovascular management survived; two demonstrated ascending aorta ecchymosis with adventitial tear and intact intima at surgery. Our results support the supposition that aortic IMH complicated with adventitial tear and partial outward seepage of IMH may generate a broken-crescent sign in CT. Despite initially stable clinical status, the residual intact inner aortic wall carries a high risk of sudden aortic rupture. CONCLUSIONS: In patients with acute aortic IMH, identification of a broken-crescent sign in CT is highly suggestive of impending aortic rupture, and early aggressive treatment is mandatory.